Analisis Komparatif Purchase Intention dan Brand Loyalty: Dikotomi Fandom CARAT dan Non-Fans sebagai Respons atas Brand Ambassador Dino SEVENTEEN - Risma Ridayanti; Anfas (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2025)
This study investigates the differences in brand loyalty and purchase intention based on consumer status as Fans or Non-Fans of a particular endorser. A quantitative method was applied to a sample of 93 people (49 Fans, 44 Non-Fans). The research instrument proved to be reliable with a Cronbach's Alpha value > 0.70. Data analysis using the Mann-Whitney non-parametric test—chosen due to the abnormality of purchase intention data in the Fan group—showed insignificant results. The significance values for brand loyalty (0.757) and purchase intention (0.121) were above the threshold of 0.05, meaning there were no substantial differences between the two groups. These findings confirm that fan labels are not key factors driving loyalty or purchase intention. Thus, company strategies should be more oriented towards other variables such as product quality, service experience, and promotional effectiveness.